Novel predictors of intravenous immunoglobulin resistance in patients with Kawasaki disease: a retrospective study - Yi, Cong; Zhou, Yu-Neng; Guo, Jun; Chen, Jia; She, Xiang (Frontiers in Immunology, 2024)
The aim of this study was to investigate the predictive value of systemic immune inflammation index (SII), systemic inflammatory response index (SIRI), and pan-immune inflammation value (PIV) in predicting intravenous immunoglobulin (IVIG) resistance in children diagnosed with Kawasaki disease (KD). Methods: The clinical data of pediatric patients diagnosed with Kawasaki disease and admitted to our hospital between January 2006 and December 2022 were retrospectively analyzed. Results: In total, 771 children diagnosed with KD were included in this study, 86 (11.2%) of whom were diagnosed with IVIG resistance. The correlation between SII, SIRI, PIV and IVIG resistance was evaluated using univariate testing, binary logistic regression analysis, and receiver operating characteristic (ROC) curve analysis. Our study found that the SII, SIRI, and PIV were independent risk factors (p=0.001, p<0.001, and p=0.02, respectively). The area under the ROC curve (AUC) values of the SII, SIRI, and PIV were 0.626 (95% confidence interval (CI): 0.553-0.698, p<0.001), 0.571 (95% CI: 0.500-0.642, p=0.032), and 0.568 (95% CI: 0.495-0.641, p=0.040), respectively, and the cutoff values were 2209.66, 3.77, and 1387.825, respectively.The SII, SIRI, and PIV have potential value in predicting IVIG resistance in patients with KD.